2019
DOI: 10.1016/j.chom.2019.02.013
|View full text |Cite
|
Sign up to set email alerts
|

NLRP12 Regulates Anti-viral RIG-I Activation via Interaction with TRIM25

Abstract: Highlights d NLRP12 reduces interferon and cytokine responses to RNA viruses and 5 0 ppp-dsRNA d NLRP12 associates with TRIM25 to disrupt Lys63 ubiquitination and activation of RIG-I d Vesicular stomatitis virus (VSV) infection downregulates NLRP12 d Myeloid-specific Nlrp12-deficient mice have increased resistance to VSV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 53 publications
0
66
0
Order By: Relevance
“…Consistently, higher inflammatory responses in Nlrp12 -/mice during Salmonella Typhimurium infection helped resolve the infection [70]. A recent study demonstrated that NLRP12 dampens antiviral immune responses; however, such a regulation involved the RIG-I pathway but not NF-κB and MAPK [75], suggesting that NLRP12 may regulate inflammatory response and host immunity in multiple ways.…”
Section: Nlrp12 and Inflammatory Disordersmentioning
confidence: 80%
“…Consistently, higher inflammatory responses in Nlrp12 -/mice during Salmonella Typhimurium infection helped resolve the infection [70]. A recent study demonstrated that NLRP12 dampens antiviral immune responses; however, such a regulation involved the RIG-I pathway but not NF-κB and MAPK [75], suggesting that NLRP12 may regulate inflammatory response and host immunity in multiple ways.…”
Section: Nlrp12 and Inflammatory Disordersmentioning
confidence: 80%
“…Formation of NLRP12 inflammasome can activate caspase 1 [54,55], which produces interleukin and leads to cell death. But NLRP12 can also form mixed inflammasomes with other NLRPs, including NLRP3, and then play an inhibitory role [56,57]. NLRP12 is also involved in adaptative immunity and controls MHC class I expression through a yet ill-defined mechanism [58].…”
Section: Clpro Cleaves Tab1 and Nlrp12mentioning
confidence: 99%
“…To date, most studies have implicated TRIM25 as a critical mediator of innate immune signalling through ubiquitination of RIG-I [2,11,[101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118], while only a handful of studies have proposed RIG-I-independent mechanisms [46,119]. Recent years have brought both exciting discoveries and rousing controversies regarding how ubiquitin and E3 ligases precisely function to activate RIG-I for antiviral signalling, with some groups suggesting a single factor operates as the critical component while others have put forth a cooperative model based on trends gleaned from numerous studies.…”
Section: Innate Antiviral Signalling Functions Of Trim25: Rig-i-depenmentioning
confidence: 99%
“…Additional evidence showing regulation of RIG-I by TRIM25 comes from studies that have uncovered several host proteins that regulate the E3 ligase activity of TRIM25 (e.g. NDR2, NLRP12, Caspase-12, Lnczc3h7a), thereby affecting downstream activation of RIG-I [103,114,[116][117][118]. Furthermore, direct interactions between endogenous TRIM25 and RIG-I have been demonstrated during viral infection [105,110].…”
Section: Innate Antiviral Signalling Functions Of Trim25: Rig-i-depenmentioning
confidence: 99%